Une Joute verbale traditionnelle de Côte d’Ivoire sur internet à l’aube des années 2000 - Derive, Jean (Tydskrif vir Letterkunde, 2014)
This paper deals with a genre consisting in a traditional contest of conventional insults produced in Ivory Coast and called gategate (insulting is translated gâter le nom in local French). The gate-gate, born in an urban context of interethnic and interlinguistic hybridity, is performed in a variant of local popular French called Nouchi (a sort of pidgin, mixing French and main local languages: Agni-Baoulé, Bété, Dioula, Gouro …) and mainly used by young people. This genre appeared in the 1990s when the political perturbations began in Ivory Coast after the death of President Houphouet-Boigny. In the early 2000, it migrated to the web to be practiced by the Ivorian diaspora dispersed across the world. This study analyses how the web promotes the rules of the gate-gate in form and content, with the modalities of communication specific to this new media, as well as the evolution of this genre’s functions, which becomes a sign of cultural solidarity and complicity.